Теоретичні основи управління фінансовими ризиками підприємства - Письменна, Т. В.; Pysmenna, Т. (КНТУ, 2015)
У статті досліджено понятійний апарат у сфері управління ризиками. Розглянуто склад системи управління фінансовими ризиками на підприємстві. Визначено ціль і завдання управління фінансовими ризиками підприємства. Досліджено принципи побудови системи управління фінансовими ризиками на підприємстві. Зроблено висновок про дискусійність і масштабність проблеми управління фінансовими ризиками підприємства. The purpose of scientific investigation is substantiating theoretical bases of financial risk management of enterprise. To achieve it necessary to reveal the essence of the term «financial risk management» and define the goal, objectives and principles of financial risk management of enterprise. The author studies some terms such as «risk management», «system of risk management», «risk-management», «risk management in the financial sector», «financial risk management» and others. The main purpose and the basis tasks of financial risk management of enterprise are determined. The principles on which must build a system of financial risk management of enterprise are investigated. The author is concluded that the whole conceptual apparatus in risk management is great and each of the terms is multifaceted. It is proved that problem of determining the goal, objectives and principles of financial risk management of enterprise have a discussion character.
Theoretical Basis of Financial Risk Management of Enterprise
Keywords: фінансові ризики підприємства; управління фінансовими ризиками; financial risk management of enterprise; system of financial risk management; purpose and objectives of financial risk management of enterprise; principles of financial risk management of enterprise